Electrocatalysis of Oxygen Reduction Reaction on Shape-Controlled Pt and Pd Nanoparticles—Importance of Surface Cleanliness and Reconstruction - Devivaraprasad, Ruttala; Nalajala, Naresh; Bera, Bapi; Neergat, Manoj (Frontiers in Chemistry, 2019)
Shape-controlled precious metal nanoparticles are of utmost scientific and technological importance. Due to their facet-dependent physical and chemical properties, these metal nanoparticles have tremendous implications in electrocatalysis. This review aims to discuss the strategies for synthesis of shape-controlled platinum (Pt) and palladium (Pd) nanoparticles and procedures for the surfactant removal without compromising their surface structural integrity. In particular, the effect of geometric and electronic factors of shape-controlled nanoparticles (Pt and Pd) on oxygen reduction reaction (ORR) is discussed and the results are correlated with that of single crystal surfaces widely reported in the literature. Accepted theories on the stability of precious metal nanoparticle surfaces under electrochemical conditions are revisited. Dissolution, reconstruction, and comprehensive views on the factors that contribute to the loss of electrochemically active surface area (ESA) of nanoparticles leading to an inevitable decrease in ORR activity are presented. The contribution of adsorbed electrolyte anions, in-situ generated adsorbates and contaminants towards the ESA reduction are also discussed. Methods for the recovery of active sites on shape-controlled Pt nanoparticles without perturbing the surface structure and its implications to electrocatalysis are reviewed.